Evolving Role of Ultrasound Elastography in Breast Imaging. - Creech, Kelsey (Radiologic Technology)
The article focuses on the evolving role of ultrasound elastography in breast imaging, highlighting its ability to assess tissue stiffness to improve diagnostic accuracy and reduce unnecessary biopsies. Elastography, integrated into sonography systems, includes two main types: strain elastography, which relies on manual compression to provide qualitative or semi-quantitative data, and shear wave elastography (SWE), which uses acoustic pulses for quantitative, operator-independent measurements. Both techniques show comparable diagnostic accuracy in differentiating benign from malignant breast lesions, with SWE offering greater reproducibility and strain elastography higher specificity. Despite limitations such as operator dependence, especially in strain elastography, the integration of artificial intelligence (AI) shows promise in enhancing diagnostic consistency and clinical utility in breast lesion evaluation.